Degreasing and decarburization process parameter optimization method for photocuring 3D printing silicon nitride ceramic
Through thermal gravity and differential thermal analysis, the degreasing process is optimized in segments, and combined with decarbonization treatment, the problem of ceramic performance failure and defects in the degreasing process in photocured 3D printed silicon nitride ceramics is solved, and the improvement of ceramic molding quality and optimization of mechanical properties is achieved.
Patent Information
- Application Number
- CN202510092954.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
During the photocuring 3D printing of silicon nitride ceramics, the green ceramics contain 20%-30% polymer organic matter such as resin, resulting in the ceramic performance that cannot meet the design and use requirements. At the same time, the degreasing process requires precise control of temperature and rate to avoid defects such as deformation and cracking of ceramics during sintering.
The temperature interval of the degreasing process is determined through thermal gravimetric and differential thermal analysis, and the temperature interval is optimized in segments. Each degreasing process adopts a different heating rate to ensure that the degreased ceramics have no external defects. Then, determine whether the ceramic has carbonization phenomenon. If so, perform a decarbonization process, and perform decarbonization in an air atmosphere through a tube furnace. The optimal decarbonization process is determined as room temperature-600℃, 1℃/min heating rate, and keep it in heat at 600℃ for 180 minutes.
It improves the molding quality of the ceramic, avoids deformation and cracking defects of the ceramic during degreasing, and ensures that the mechanical properties of the ceramic meet the design requirements.
Smart Images

Figure CN119874383A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon nitride sintering, and in particular to a method for optimizing process parameters of degreasing and decarburization of photocurable 3D printed silicon nitride ceramics. Background Art
[0002] 3D printing is widely used due to its unique advantages: customization, low loss, and precise molding of complex structures. Among them, photocuring molding has attracted much attention from scientific researchers due to its printing flexibility, high precision, and fast printing speed. However, after the ceramic green body is obtained by photocuring 3D printing, the green body often contains 20wt%-30wt% of resin and other high molecular organic matter. At this time, the performance of the ceramic cannot meet the design and use requirements. In order to meet the mechanical property requirements and normal use of the ceramic, it is necessary to discharge the organic matter inside the green body through the degreasing process. However, during the degreasing process, the organic matter in the binder of the silicon nitride ceramic powder will be discharged from the ceramic green body through physical and chemical changes such as volatilization, melting and cracking, causing the ceramic green body to shrink and become dense. At the same time, defects are very likely to occur in the ceramic green body. Therefore, during the degreasing process, the degreasing temperature and degreasing rate need to be precisely controlled to optimize the degreasing process parameters to avoid external defects such as deformation and cracking of the ceramic during the sintering process due to too fast a rate, and to avoid problems such as too high degreasing costs and experimental cycles caused by too slow a heating rate.
[0003] Due to the different organic matter contents inside the photocuring printed silicon nitride ceramic body, some ceramics will not show carbonization on their surface after the degreasing process because the organic matter is not completely discharged and transferred to the surface. However, for silicon nitride ceramics that need to undergo a decarburization process, it is necessary to determine an optimized decarburization process to remove the carbonized organic matter on the surface of the silicon nitride ceramic, so as to achieve the purpose of obtaining ceramic materials that meet the performance requirements through the optimized decarburization process.
[0004] Literature 1 "Pan Huan, Lu Bingheng, Bao Chonggao, et al. A high-thickness and high-strength photocured silicon nitride ceramic and its preparation method [P]. Shaanxi Province: CN202011272964.3, 2024-10-01", through its optimized degreasing method, the maximum degreasing thickness of silicon nitride ceramics is increased to 8mm, and the degreasing time is only 60h, and the degreasing rate can reach more than 99%.
[0005] Document 2 "Bao Chonggao, Tu Youpeng, Li Shijia. Photocured silicon oxynitride ceramic slurry, preparation and preparation method of porous ceramics with complex structures [P]. Shaanxi Province: CN202410536925.1, 2024-08-02" A method for preparing porous ceramics with complex structures using slurry, including printing, degreasing and sintering processes.
[0006] Reference 3 "Chen Yingjie. Controllable preparation and performance study of photocurable 3D printed silicon nitride ceramic slurry [D]. Yancheng Institute of Technology, 2024. DOI: 10.44381 / d.cnki.gycit.2024.000129" studied the influence of oxidation pretreatment of Si3N4 powder and silane coupling agent modification on the rheological properties and curing properties of the slurry, and discussed the action mechanism of resin type and ratio, different dispersants and photoinitiators on ceramic slurry, providing basic data for reference for the preparation of Si3N4 ceramic slurry with high solid content and low viscosity, and revealing the influence mechanism of different degreasing and sintering processes on the mechanical properties and density of Si3N4 ceramics.
[0007] Document 4 "Bai Yujun, Bi Jianqiang, Qi Yongxin, et al. A method for preparing silicon nitride powder material at low temperature [P]. Shandong: CN200810015630.0, 2008-09-10" invented a method for preparing silicon nitride powder material at low temperature. After the silicon nitride powder material is subjected to a decarbonization process, the product has good chemical stability, high yield and high powder size control effect.
[0008] Document 5 "Zhang Wenfa, Wang Mouhua, Zhang Wenli, et al. A silicon nitride fiber and a preparation method thereof [P]. Shanghai: CN201610848803.1, 2018-04-03" invented a silicon nitride fiber and a preparation method thereof. The preparation method comprises the following steps: (1) cross-linking the polycarbosilane fiber under electron beam radiation to obtain an infusible polycarbosilane fiber; (2) nitriding and decarburizing the infusible polycarbosilane fiber under an ammonia atmosphere; (3) sintering under an inert atmosphere; (4) cooling to room temperature under an inert atmosphere to obtain silicon nitride fiber. The silicon nitride fiber prepared by the preparation method provided by the present invention has low oxygen content, high tensile strength, and excellent high temperature resistance.
[0009] Reference 6 "Chen Ping. Research on Sialon Ceramic Injection Molding and Degreasing Process [D]. Jiangsu University, 2010", uses solvent degreasing method to degreasing silicon nitride ceramics, examines the effects of degreasing temperature, degreasing time, degreasing solvent concentration, sample thickness, solvent addition method and surface area to volume ratio on the degreasing of the green body in the solvent degreasing process in injection molding, and makes a preliminary analysis of the maximum removal rate of soluble components in the solvent degreasing process.
[0010] Reference 7 "Jin Bocheng. Photocuring 3D printing preparation and mechanical properties of silicon nitride ceramics [D]. Shanghai University of Technology, 2022. DOI: 10.27801 / d.cnki.gshyy.2022.000173", studied the heat treatment process of photocuring silicon nitride ceramic blanks. First, the effects of debinding atmosphere and heating rate on the samples were studied to determine the optimal debinding process system. Afterwards, the DLP molding parameters were optimized, and the three-point bending strength was used as the evaluation index. Under the printing conditions of 25μm layer thickness and single-layer curing time of 8s, the sintered silicon nitride ceramics had the maximum three-point bending strength. During the debinding process in an inert atmosphere, carbon residue was found in the blank. Through comparative experiments, it was confirmed that these carbon elements can participate in the carbon thermal reduction reaction during high-temperature sintering and cause defects such as interlayer cracking and deformation in the blank. According to the thermogravimetric curve of the carbon-containing body in air atmosphere, under the process conditions of low-temperature oxidation of 450℃ and oxidation time of 5h, the carbon element in the silicon nitride body can be effectively removed without oxidation reaction. Finally, the effect of sintering temperature on the mechanical properties of silicon nitride ceramics was studied. At a sintering temperature of 1850℃, the relative density of silicon nitride ceramics was 94.5%, and the three-point bending strength reached 441MPa.
[0011] Reference 8 "Zhou, Maopeng, Liu, Wei, Wu, Haidong, et al. Preparation of adefect-freealumina cutting tool via additive manufacturing based on stereolithography-Optimization of the drying and debinding processes[J]. CERAMICSINTERNATIONAL, 2016, 42, (10): 11598-11602. DOI: 10.1016 / j.ceramint.2016.04.050", a dense and defect-free alumina cutting tool was manufactured by stereolithography. Then different drying processes and debinding curves were tested and compared to find the best method for preparing the sintered body. The experimental results show that the use of PEG400 as a liquid desiccant can reduce body deformation compared with the natural drying process. Compared with vacuum debinding or air debinding, a two-step debinding process consisting of a vacuum pyrolysis step and a subsequent air debinding step is allowed to control the pyrolysis rate while suppressing the formation of defects in the alumina body. After optimized post-processing, the relative density of the sample is as high as 99.3%, with a Vickers hardness of 17.5 GPa. These properties are similar to those of alumina bodies prepared by traditional molding methods.
[0012] Reference 9 "Wang, Kejie, Liu, Rongzhen, Xu, Haiman. High-strength and wave-transmitting Si3N4-Si2N2O-BN composites prepared using selective lasersintering[J]. CERAMICSINTERNATIONAL, 2022, 48, (14): 20126-20133. DOI: 10.1016 / j.ceramint.2022.03.291", studied the successful development of high-strength and wave-transmitting silicon nitride (Si3N4) composites by selective laser sintering (SLS) and cold isostatic pressing (CIP) after debinding and before final sintering, and determined the optimal forming process parameters of SLS-Si3N4 ceramics. The effects of sintering aids and secondary CIP on the bulk density, porosity, flexural strength, fracture toughness and wave transmission properties of Si3N4 composites were studied.
[0013] Reference 10 "Jin, B. Bian, Y. Shen, Y. et al. Improved Flexural Strength in Digital-Light-Processing-Printed Si3N4 Ceramics by Removing Carbon Residue[J]. JOURNALOF CERAMIC SCIENCE AND TECHNOLOGY, 2022, 13, (2): 99-106. DOI: 10.4416 / JCST2022-00001" proposes a method for eliminating residual carbon in silicon nitride compacts manufactured using stereolithography. According to thermogravimetric analysis in an air atmosphere, the amount of carbon residue remaining in the debonded silicon nitride body was 0.58%. When the oxidation temperature and the holding time in air were 450°C and 5h, respectively, the residual carbon in the sample could be fully removed. The flexural strength of the sintered ceramic without removing the carbon residue is only 184.88±8.16MPa; the flexural strength of the sintered silicon nitride ceramic after removing the carbon residue can reach 469.78±11.86MPa.
[0014] Through the above literature research and analysis, it is found that although there have been many related works on the optimization of silicon nitride ceramic debinding process, there are few detailed optimization analyses of the decarburization process after debinding, and there are also few works in many silicon nitride ceramic decarburization process optimization works that consider the detailed optimization methods of the debinding process. Summary of the invention
[0015] Based on the technical problems existing in the background technology, the present invention proposes a method for optimizing the process parameters of degreasing and decarburization of photocuring 3D printed silicon nitride ceramics, determines the optimized process of degreasing and decarburization of ceramics, and improves the molding quality of ceramics.
[0016] The method for optimizing process parameters of degreasing and decarburizing silicon nitride ceramics for photocuring 3D printing proposed by the present invention comprises the following steps:
[0017] Step 1: Perform thermogravimetric and differential thermal analysis on the ceramic green body to determine the degreasing process temperature range and divide the degreasing temperature range into sections;
[0018] Step 2: Degreasing the ceramics in sections based on the sectioned degreasing process, optimizing each section of the degreasing process to determine the optimal degreasing process;
[0019] Step 3: Determine whether carbonization occurs in the ceramic after the degreasing process is optimized, and remove organic matter from the carbonized ceramic through the decarbonization process to complete the degreasing and decarbonization process of the ceramic.
[0020] Furthermore, in step one, the degreasing process temperature range and the degreasing temperature range segmentation are determined as follows: based on the results of thermogravimetric and differential thermal analysis, the weight loss rates of the TG curve and the DTG curve in the silicon nitride ceramic degreasing process are analyzed to be greater than 0.02% / °C, and the weight loss peak existing in the DTG curve is greater than the preset threshold peak value, and the degreasing process temperature range is determined based on the standard that the mass decreases slowly after the temperature increases; and the degreasing process temperature range is segmented according to the distribution of the exothermic characteristic peaks.
[0021] Furthermore, in step one, the thermogravimetric and differential thermal analysis is specifically as follows: placing the ceramic green body in a thermogravimetric and differential thermal analyzer for constant heating, selecting an air atmosphere as the heating environment, selecting a heating rate of 5°C / min, and selecting a heating range of room temperature to 800°C.
[0022] Furthermore, in step 2, the optimization process of each degreasing process is as follows:
[0023] (a1) judging the degreasing process of the current segment based on whether there are external defects after the degreasing of the ceramic of the current segment, and entering (a2) when there are external defects, and entering (a3) when there are no external defects;
[0024] (a2) optimizing the degreasing process of the current segment, and degreasing the ceramic of the current segment again until no external defects exist;
[0025] (a3) The degreasing process optimization of the current segmented ceramics is completed;
[0026] (a4) The next segmented ceramic is used as the current segmented ceramic, and the process from (a1) to (a4) is repeated until the debinding process optimization of all segments is completed.
[0027] Furthermore, the degreasing process is carried out under a nitrogen atmosphere, and the degreasing temperature range is divided into four sections: room temperature-150°C, 150°C-300°C, 300°C-500°C and 500°C-800°C; the degreasing process after optimization in each section is as follows:
[0028] The room temperature-150℃ is used as the first degreasing temperature range. The optimized degreasing process corresponding to the first degreasing temperature range is: heating rate 0.6℃ / min, keeping at 150℃ for 30min;
[0029] The second degreasing temperature range is 150℃-300℃. The optimized degreasing process corresponding to the second degreasing temperature range is: heating rate 0.3℃ / min, keeping at 300℃ for 30min;
[0030] The second degreasing temperature range is 300℃-500℃, and the optimized degreasing process corresponding to the third degreasing temperature range is: heating rate 0.2℃ / min, keeping at 500℃ for 30min;
[0031] The third degreasing temperature range is 500℃-800℃, and the optimized degreasing process corresponding to the fourth degreasing temperature range is: heating rate 0.3℃ / min, keeping at 800℃ for 30min.
[0032] Further, in step three, the ceramic decarburization process is as follows:
[0033] The degreased ceramics are placed in a tubular furnace for decarburization. The environment is air atmosphere. The temperature is increased at a rate of 1°C / min from room temperature to 600°C, and the decarburization process is carried out at 600°C for 180min, 240min, 300min, and 400min respectively. The optimal decarburization process is determined as follows: the decarburization temperature is room temperature to 600°C, the heating rate is 1°C / min, and it is kept at 600°C for 180min, and then cooled with the tubular furnace.
[0034] The advantages of the method for optimizing the process parameters of degreasing and decarburization of silicon nitride ceramics for photocuring 3D printing provided by the present invention are as follows: the method for optimizing the process parameters of degreasing and decarburization of silicon nitride ceramics for photocuring 3D printing provided in the structure of the present invention analyzes the quality change of the ceramic green body by the TG-DTG result, and determines the degreasing process temperature range based on the standard that the quality will not change significantly with the increase of temperature; analyzes the distribution of the exothermic characteristic peak by the TG-DTG result, and performs segmented processing on the ceramic degreasing temperature range; selects different heating rates for the segmented temperature range, and performs degreasing experiments based on the standard that the sample after degreasing has no obvious external defects; after completing the above steps, the silicon nitride ceramic needs to observe whether the ceramic green body has obvious carbonization phenomenon, and if so, decarburization treatment is required, and if not, the degreasing process is completed, thereby improving the molding quality of the ceramic, and providing a highly feasible solution for the degreasing and decarburization process of photocuring printed silicon nitride ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the process of the present invention;
[0036] Figure 2 This is the TG-DTG analysis diagram of silicon nitride ceramics. The black curve corresponds to the TG curve, and the red curve corresponds to the DTG curve.
[0037] Figure 3 This is the process curve of ceramic degreasing and decarburization. DETAILED DESCRIPTION
[0038] Below, the technical solution of the present invention is described in detail through specific embodiments. Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific implementation disclosed below.
[0039] like Figure 1 , 2 As shown in 3, the method for optimizing the process parameters of degreasing and decarburization of light-cured 3D printed silicon nitride ceramics proposed in the present invention comprises the following steps:
[0040] Step 1: Perform thermogravimetric and differential thermal analysis on the ceramic green body to determine the degreasing process temperature range and divide the degreasing temperature range into sections;
[0041] Thermogravimetric and differential thermal analysis (TG-DTG) is specifically as follows: the ceramic green body is placed in a thermogravimetric differential thermal analyzer for constant heating, the heating environment is selected as an air atmosphere, the heating rate is selected as 5°C / min, and the heating range is selected as room temperature (RT) - 800°C.
[0042] The debinding process temperature range and the debinding temperature range segmentation are determined as follows: according to the results of thermogravimetric and differential thermal analysis, the range where the quality of silicon nitride ceramics is significantly reduced in the debinding process is analyzed, and the debinding process temperature range is determined based on the standard that the quality reduction is not obvious after the temperature is increased; and then the debinding process temperature range is segmented according to the distribution of the exothermic characteristic peak. Figure 2 As shown, the obvious quality decline mainly refers to that the weight loss rate of the TG curve and the DTG curve is greater than 0.02% / ℃, and the weight loss peak in the DTG curve is greater than the preset threshold peak value (that is, there is a more obvious weight loss peak). The insignificant quality decline is mainly because the TG curve and the DTG curve tend to be stable with the increase of temperature (that is, the quality decline is not obvious).
[0043] Thermogravimetric and differential thermal analysis results are as follows Figure 2 As shown in the figure, the temperature range with the most obvious quality degradation is room temperature (RT) - 800℃, and the exothermic peaks are 110℃, 300℃ and 360℃. Therefore, the degreasing temperature range is determined to be: room temperature (RT) - 800℃, and the degreasing temperature range is divided into the following 4 temperature ranges: RT-150℃, 150℃-300℃, 300℃-500℃ and 500℃-800℃.
[0044] Step 2: Degreasing the ceramics in sections based on the sectioned degreasing process, optimizing each section of the degreasing process to determine the optimal degreasing process;
[0045] The degreasing process is carried out under nitrogen atmosphere. The optimization process of each degreasing process is as follows:
[0046] (a1) judging the degreasing process of the current segment based on whether there are external defects after the degreasing of the ceramic of the current segment, and entering (a2) when there are external defects, and entering (a3) when there are no external defects;
[0047] (a2) optimizing the degreasing process of the current segment, and degreasing the ceramic of the current segment again until no external defects exist;
[0048] (a3) The degreasing process optimization of the current segmented ceramics is completed;
[0049] (a4) The next segmented ceramic is used as the current segmented ceramic, and the process from (a1) to (a4) is repeated until the debinding process optimization of all segments is completed.
[0050] For the above four temperature ranges, Figure 3 As shown, the specific steps for optimizing each degreasing process are (b1) to (b4):
[0051] (b1) The process was optimized for the first degreasing temperature range of RT-150℃. First, a faster heating rate of 1.5℃ / min was selected. In order to ensure that the inside of the ceramic can reach stability after heating, it is necessary to keep the temperature for 30 minutes after each degreasing process is completed. However, in the experiment under this degreasing process, there are obvious cracks on the surface of the silicon nitride blank. Therefore, the degreasing rate was reduced, and the heating rates of 1℃ / min, 0.8℃ / min and 0.6℃ / min were selected respectively. Finally, it was found that there were no obvious defects on the ceramic surface after degreasing with a heating rate of 0.6℃ / min and keeping at 150℃ for 30 minutes. Therefore, the optimized degreasing process corresponding to the first degreasing temperature range is: heating rate 0.6℃ / min, keeping at 150℃ for 30 minutes.
[0052] (b2) The process was optimized for the second degreasing temperature range of 150℃-300℃. The initial degreasing process heating rate was 0.5℃ / min, which was slightly lower than the heating rate of the first degreasing optimization process. The experiment found that there were many surface cracks on the surface of the green body after degreasing, so the speed reduction treatment was selected. The heating rates of 0.4℃ / min and 0.3℃ / min were selected respectively, and the temperature was kept at 300℃ for 30min. The external integrity of the ceramic structure under each heating rate was compared. The optimized degreasing process corresponding to the second degreasing temperature range was: the heating rate was 0.3℃ / min, and the holding time was 30min.
[0053] (b3) The process was optimized for the third degreasing temperature range of 300℃-500℃. The initial degreasing process heating rate was selected as 0.3℃ / min. It was found that the silicon nitride ceramic body surface corresponding to this process had cracks, so a speed reduction treatment was selected, 0.2℃ / min and 0.1℃ / min were selected respectively. After comparing the surface integrity of the body after degreasing, no cracks were found. Considering the degreasing experiment cycle and cost, the optimized degreasing process corresponding to the third degreasing temperature range was: the heating rate was 0.2℃ / min, and the holding time was 30min.
[0054] (b4) The process was optimized for the fourth degreasing temperature range of 500℃-800℃. The initial degreasing process heating rate was selected as 1℃ / min. It was found that the surface of the silicon nitride ceramic body after degreasing by this process had obvious cracks. Therefore, a speed reduction treatment was selected, and 0.6℃ / min, 0.3℃ / min and 0.2℃ / min were selected respectively. After comparing the surface integrity of the body after degreasing, it was found that the ceramic body after degreasing corresponding to 0.3℃ / min and 0.2℃ / min had no surface cracks. The optimized degreasing process corresponding to the fourth degreasing temperature range was: the heating rate was 0.3℃ / min, and the holding time was 30min.
[0055] Step 3: Determine whether carbonization occurs in the ceramic after the degreasing process is optimized, and remove organic matter from the carbonized ceramic through the decarbonization process to complete the degreasing and decarbonization process of the ceramic.
[0056] like Figure 3 As shown in the figure, the decarburization process of ceramics is as follows: first, analyze whether carbonization occurs in silicon nitride ceramics during the degreasing process. If so, a decarburization process is required. If not, the degreasing process of silicon nitride ceramics is optimized. The experiment found that obvious carbonization occurs on the surface of silicon nitride ceramics after the degreasing process is completed, so a decarburization process is required. The degreased silicon nitride ceramics are placed in a tubular furnace for decarburization. The environment is an air atmosphere. The temperature is increased at a rate of 1°C / min from room temperature (RT) to 600°C, and the decarburization process is analyzed at 600°C for 180min, 240min, 300min, and 400min of insulation. After comparison, it is found that the above decarburization processes all achieve the decarburization function. Considering the decarburization process cycle and experimental cost, the decarburization process is determined as follows: the decarburization temperature is room temperature (RT)-600°C, the heating rate is 1°C / min, and it is kept at 600°C for 180min.
[0057] In this embodiment, the quality change of the ceramic green body is analyzed based on the TG-DTG results, and the degreasing process temperature range is determined based on the standard that the quality will not change significantly with the increase of temperature; the distribution of the exothermic characteristic peaks is analyzed based on the TG-DTG results, and the ceramic degreasing temperature range is segmented; different heating rates are selected in the segmented temperature range, and the degreasing experiment is carried out based on the standard that the sample after degreasing has no obvious external defects; after completing the above steps, the silicon nitride ceramic needs to be observed for whether the ceramic green body has obvious carbonization phenomenon. If so, decarbonization treatment is required, and if not, the degreasing process is completed, which provides a highly feasible solution for the degreasing and decarbonization process of photocuring printing silicon nitride ceramics.
[0058] The process optimization method proposed in this embodiment optimizes the segmented degreasing process of silicon nitride ceramics through TG-DTG analysis results, and obtains the optimization curve of silicon nitride degreasing process based on whether there are obvious defects on the outside of the green body after degreasing. In addition, this embodiment discusses the removal scheme of residual organic matter inside silicon nitride ceramics after the degreasing process, and analyzes how to optimize the process of silicon nitride decarburization, providing a more reliable practical guidance for silicon nitride degreasing and decarburization processes. At the same time, compared with other process optimization methods, this embodiment has the advantages of strong practicality and comprehensive analysis.
[0059] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for optimizing process parameters of degreasing and decarburization of light-cured 3D printed silicon nitride ceramics, comprising the following steps: Step 1: Perform thermogravimetric and differential thermal analysis on the ceramic green body to determine the degreasing process temperature range and divide the degreasing temperature range into sections; Step 2: Degreasing the ceramics in sections based on the sectioned degreasing process, optimizing each section of the degreasing process to determine the optimal degreasing process; Step 3: Determine whether carbonization occurs in the ceramic after the degreasing process is optimized, and remove organic matter from the carbonized ceramic through the decarbonization process to complete the degreasing and decarbonization process of the ceramic.
2. The method for optimizing process parameters of light-cured 3D printing silicon nitride degreasing and decarburization according to claim 1, characterized in that: In step one, the degreasing process temperature range and the degreasing temperature range segmentation are determined as follows: based on the results of thermogravimetric and differential thermal analysis, the weight loss rates of the TG curve and the DTG curve in the silicon nitride ceramic degreasing process are analyzed to be greater than 0.02% / °C, and the weight loss peak existing in the DTG curve is greater than the preset threshold peak value, and the degreasing process temperature range is determined based on the standard that the mass decreases gradually after the temperature increases; and the degreasing process temperature range is segmented according to the distribution of the exothermic characteristic peak.
3. The method for optimizing process parameters of light-cured 3D printing silicon nitride degreasing and decarburization according to claim 1, characterized in that: In step one, the thermogravimetric and differential thermal analysis is specifically as follows: the ceramic green body is placed in a thermogravimetric and differential thermal analyzer for constant heating, the heating environment is selected as an air atmosphere, the heating rate is selected as 5°C / min, and the heating range is selected as room temperature-800°C.
4. The method for optimizing process parameters of light-cured 3D printing silicon nitride degreasing and decarburization according to claim 1, characterized in that: In step 2, the optimization process of each degreasing process is as follows: (a1) judging the degreasing process of the current segment based on whether there are external defects after the degreasing of the ceramic of the current segment, and entering (a2) when there are external defects, and entering (a3) when there are no external defects; (a2) optimizing the degreasing process of the current segment, and degreasing the ceramic of the current segment again until no external defects exist; (a3) The degreasing process optimization of the current segmented ceramics is completed; (a4) The next segmented ceramic is used as the current segmented ceramic, and the process from (a1) to (a4) is repeated until the debinding process optimization of all segments is completed.
5. The method for optimizing process parameters of light-cured 3D printing silicon nitride degreasing and decarburization according to claim 4, characterized in that: The degreasing process is carried out under nitrogen atmosphere, and the degreasing temperature range is divided into four sections: room temperature-150℃, 150℃-300℃, 300℃-500℃ and 500℃-800℃; the degreasing process after optimization in each section is as follows: The room temperature-150℃ is used as the first degreasing temperature range. The optimized degreasing process corresponding to the first degreasing temperature range is: heating rate 0.6℃ / min, keeping at 150℃ for 30min; The second degreasing temperature range is 150℃-300℃. The optimized degreasing process corresponding to the second degreasing temperature range is: heating rate 0.3℃ / min, keeping at 300℃ for 30min; The second degreasing temperature range is 300℃-500℃, and the optimized degreasing process corresponding to the third degreasing temperature range is: heating rate 0.2℃ / min, keeping at 500℃ for 30min; The third degreasing temperature range is 500℃-800℃, and the optimized degreasing process corresponding to the fourth degreasing temperature range is: heating rate 0.3℃ / min, keeping at 800℃ for 30min.
6. The method for optimizing process parameters of photocuring 3D printing silicon nitride degreasing and decarburization according to claim 1, characterized in that: In step three, the ceramic decarburization process is as follows: The degreased ceramics are placed in a tubular furnace for decarburization. The environment is air atmosphere. The temperature is increased at a rate of 1°C / min from room temperature to 600°C, and the decarburization process is carried out at 600°C for 180min, 240min, 300min, and 400min respectively. The optimal decarburization process is determined as follows: the decarburization temperature is room temperature to 600°C, the heating rate is 1°C / min, and it is kept at 600°C for 180min, and then cooled with the tubular furnace.
Citation Information
Patent Citations
Rapid degreasing and sintering method for photocuring shaped ceramic body
CN110372398A
High-thickness high-strength light-cured silicon nitride ceramic and preparation method thereof
CN114478049A
Preparation method of silicon nitride ceramic
CN115710129A
Silicon nitride sintered product and method for producing the same
JP2001181053A
Method for manufacturing sintered product from three-dimensional molded article
JP2021165216A
Cited By
Degreasing method of silicon nitride ceramic substrate
CN121850684A
Low-defect degreasing process for photocuring silicon nitride ceramic green body
CN121850693A